Perlindungan Konsumen di Sektor Jasa Keuangan Perbankan - Irma Sari Permata (FEB-UP Press, 2020)
Financial institutions of the banking sector are one of the financial institutions that serve as the measure of progress of a country. To realize the financial system that grows continuously and stable, and able to protect the interests of consumers and society, the Government established the OJK (Financial Services Authority). This research uses secondary data relating to the level of effectiveness of consumer protection of financial services. Data collection techniques through observation, library studies. The result of this research is the development of consumer complaints in the banking financial sector. It is expected that the research has increased education by conducting socialization on consumers and monitoring and surveying of banks, in order to minimize the mistakes committed by the banking sector.